2007
DOI: 10.1063/1.2764114
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic process of dendrite fragmentation in solidification from undercooled Si melt using time-resolved x-ray diffraction

Abstract: The spontaneous dendrite fragmentation in solidification from undercooled Si melt was analyzed by time-resolved two-dimensional x-ray diffractometry. For the sample solidified at ΔT=261K, several spots appeared at 1ms after recalescence and the subsequent transition from spots to rings occurred within ∼25ms, which suggests that the fragmentation occurred after recalescence but just at the initial stage of the plateau period. Although the present experiment supported that the driving force for the fragmentation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The fragmentation of thermal dendrites in pure materials in the post-recalescence plateau period would only occur in the very initial stage of the plateau period when the dendrites are characterized by the typical dendritic morphology. This was in fact verified by Ngashio et al where the dendrites in large droplets of 1.8 mm diameter fragmented in the initial 25 ms of the plateau period ( $2 s), i.e., the time for break-up was 1.25% of the plateau period [17]. Thus, when the remaining liquid solidifies, controlled mainly by the extraction of heat, the dendrites would lose their morphology and grow with a planar front.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…The fragmentation of thermal dendrites in pure materials in the post-recalescence plateau period would only occur in the very initial stage of the plateau period when the dendrites are characterized by the typical dendritic morphology. This was in fact verified by Ngashio et al where the dendrites in large droplets of 1.8 mm diameter fragmented in the initial 25 ms of the plateau period ( $2 s), i.e., the time for break-up was 1.25% of the plateau period [17]. Thus, when the remaining liquid solidifies, controlled mainly by the extraction of heat, the dendrites would lose their morphology and grow with a planar front.…”
Section: Discussionmentioning
confidence: 69%
“…The supercoolings predicted by the nucleation kinetics model were 226 K for 275 mm droplet and 320 K for the 200 mm droplet. At these high supercoolings, previous studies [17,18] have also reported formation of /100S orthogonal dendrites. However, a more rigorous verification of the actual numerical values from the CCT curves was not possible due to the height and temperature limitations of the present UDS apparatus.…”
Section: Dendrite Fragmentationmentioning
confidence: 79%
See 1 more Smart Citation
“…Dendrite structures, which are highly hierarchical branched patterns with primary-, secondary-and higherorder branches, are of immense practical importance in determining the engineering properties of materials that solidify dendritically [1][2][3]. Studying the dendritic growth has also been of long-standing fundamental interest because of the ubiquity of branched structures exhibited by diverse interfacial pattern formation systems, and discovering how crystals grow, develop, and create such complex patterns has been a challenge to researchers in crystalline materials for several centuries [4][5][6][7][8][9][10]. Considering the crystallization from liquids should be mostly determined by the heat and solute diffusions at the interfaces, the crystalline microstructure should be the result of the morphological instability of the solid-liquid interface.…”
Section: Introductionmentioning
confidence: 99%